Por um incidente de ilicitude probatória no processo penal - Eberhardt, Marcos Eduardo Faes (2022)
The research raises as its issue the rethinking of the care with illicit evidence in the Brazilian criminal procedure, having as its main objective to understand the normative, jurisprudential and doctrinal treatment of the theme, starting from the hypothesis that there is a crisis in the Brazilian evidentiary system that has significantly reduced the importance of evidential illicitness as an autonomous legal institute. The specific objectives cross to diagnose: (1) whether there is an effective control on the admissibility of evidence in the Brazilian criminal process, enabling a procedural treatment to substantiated allegations of evidentiary unlawfulness, mainly considering the way of entry by joining to the records in relation to the category of means for obtaining evidence (2) whether it is possible to identify, contemporaneously, a tendency in relation to the law of evidence, at first looking outward, through the American exclusionary rules, and then looking inward, evaluating whether an external phenomenon (new trends in North American jurisprudence) may indicate a direction for the Brazilian criminal procedure system on the subject of illicit evidence (3) the normative, doctrinaire and jurisprudential treatment given by the Brazilian Federal Supreme Court, in the field of evidentiary irregularities, since the validity of the 1941 Code of Criminal Procedure, reaching the post-accusatory period in Brazil (4) whether these treatment parameters demonstrate the displacement of the issue of unlawful evidence in relation to the final act and the detachment of its analysis from the valuation of evidence (free judicial conviction) (5) whether there is a normative void in cases of evidentiary unlawfulness in Brazil from the point of view of the procedural treatment of allegations of illicit evidence. These problems were answered in three chapters, using a bibliographic review and analysis of decisions by the Brazilian Federal Supreme Court, employing the hypothetical-deductive method. Based on the diagnoses, the guidelines for the design of an incidental procedural treatment to the allegations of illicit evidence in the Brazilian criminal process were presented. Keywords: Evidentiary irregularity; Evidence nullity; Illicitly of evidence; Illicit evidence; Probatory incident.